2018
DOI: 10.3171/2018.9.focus18380
|View full text |Cite
|
Sign up to set email alerts
|

Return-to-active-duty rates after anterior cervical spine surgery in military pilots

Abstract: OBJECTIVESymptomatic cervical spondylosis with or without radiculopathy can ground an active-duty military pilot if left untreated. Surgically treated cervical spondylosis may be a waiverable condition and allow return to flying status, but a waiver is based on expert opinion and not on recent published data. Previous studies on rates of return to active duty status following anterior cervical spine surgery have not differentiated these rates among military specialty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…Success of an orthopaedic procedure is often dictated by the rate by which patients return to full function (such as preinjury levels of physical activity, or in the case of athletes, the rate of return to sport). In the military, return to duty is commonly reported as a way of describing a patient’s return to full function, or even equated to return to sport [2-4, 7, 11, 15, 19-24, 26, 29-32, 34-36, 38]. Because military studies often are used as a part of systematic reviews or meta-analyses that encompass both military and civilian patients, return to duty is a relevant outcome measure for civilian and military readers alike as they attempt to interpret these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Success of an orthopaedic procedure is often dictated by the rate by which patients return to full function (such as preinjury levels of physical activity, or in the case of athletes, the rate of return to sport). In the military, return to duty is commonly reported as a way of describing a patient’s return to full function, or even equated to return to sport [2-4, 7, 11, 15, 19-24, 26, 29-32, 34-36, 38]. Because military studies often are used as a part of systematic reviews or meta-analyses that encompass both military and civilian patients, return to duty is a relevant outcome measure for civilian and military readers alike as they attempt to interpret these studies.…”
Section: Discussionmentioning
confidence: 99%
“…In athletes, this may be further specified in terms of the likelihood and timing of return to sport. In the military, a commonly used metric of functional outcome after orthopaedic surgery is return to duty [2-4, 7, 11, 15, 19-24, 26, 29-32, 34-36, 38]. Return to duty is an easily collectable data point for military patients, as soldiers who are unable to return to their physical duties are placed on a trackable mandated activity restriction, called a physical profile, which prevents them from participating fully in fitness requirements (such as group physical training, group sports, and the twice-yearly graded physical fitness test).…”
Section: Introductionmentioning
confidence: 99%
“…The normal acceleration magnitude during ejection from the seat is 12 to 14 + Gz, and parachute opening shock can range from 10 to 20 + Gz [7]. Vertebral fractures occur frequently with forces greater than 20 + Gz, but with poor positioning, forces as low as 10 + Gz have caused fractures [7]. Sommer et al [14] found that military aircrew had a high risk of spinal injuries (56.3%) after emergency evacuation using an ejection seat, including spinal fracture, soft tissue injury, and disc herniation.…”
Section: Aeromedical Considerations About Ldh and Lismentioning
confidence: 99%
“…Studies have reported that the onset age of cervical spondylosis in military pilots is earlier than that of ordinary people, and the incidence of cervical spondylosis increases significantly after the age of 30.In this study, the onset of cervical spondylosis was earlier in military pilots, and the cervical cervical "premature senescence" was most obvious in the early stage of military pilots's career [12] .In the study of the risk factors of cervical vertebra disease among military pilotsof different aircraft classes, there was no difference in the age of onset of cervical vertebra disease among different aircraft classes, and age may not be a risk cervical fusion, but no other details were provided [13] . Miller [14] conducted a single-center retrospective study on active pilots in the US military who received ACDF or CTDR from January 2010 to June 2017. The proportion of military pilots returning to active flight status after anterior cervical surgery was 84.6%.…”
Section: Discussmentioning
confidence: 99%